The Modulation of Laser Refractive Surgery on Sensory Eye Dominance of Anisometropia - Hongting Liu; Qi Chen; Fangfang Lan; Yan Luo; Enwei Lin; Wuqiang Luo; Ming Kong; Jiangxia Wang; Fengju Zhang (Journal of Ophthalmology)
Purpose. To evaluate the effect of laser refractive surgery on sensory eye dominance of anisometropia. Methods. A total of 156 subjects with nonanisometropic myopia and 70 subjects with anisometropic myopia were enrolled in the first part of the study. The dichoptic motion coherence threshold technique was applied to collect the normal dataset and distribution of sensory eye dominance. The second part of the study included 40 subjects with nonanisometropic myopia and 40 subjects with anisometropic myopia who received the femtosecond laser-assisted in situ keratomileusis (Fs-LASIK). A comprehensive ophthalmologic evaluation was performed with particular attention to sensory eye dominance preoperatively and one-week and one-month postoperatively. The ocular dominance index (ODI) was applied to evaluate the subject’s overall degree of sensory ocular dominance. Visual acuity, sighting eye dominance, and stereo acuity were also accessed. Results. In experiment one, the mean ODI in the nonanisometropic group and the anisometropic group was 1.48 ± 0.63 and 1.95 ± 1.07, respectively. The ODI values of the anisometropic group were significantly higher than those of the nonanisometropic group (Mann–Whitney U test, P<0.001). The demographics information and the distribution of ODI values in both groups are summarized in tables and figures. In experiment two, all LASIK procedures were uneventful and no postoperative complications were observed during the postoperative follow-up. Preoperatively, the ODI values of the anisometropic LASIK group were significantly higher than those of the nonanisometropic LASIK group, which was consistent with the results of part 1. However, one week after operation, the mean ODI values of the anisometropic LASIK group had significantly decreased from 1.89 ± 1.09 to 1.39 ± 0.44. And, the mean ODI values slightly increased to 1.65 ± 0.61 one-month postoperatively. In the nonanisometropic LASIK group, there were no statistically significant differences of ODI changes among preoperative, post-one-week and post-one-month visits. The demographics information and the changes of ODI of both LASIK groups are summarized in tables and figures. Conclusion. Stronger sensory eye dominance is seen in the subjects with anisometropic myopia compared to subjects with nonanisometropic myopia. The strong sensory dominance of anisometropia becomes more balanced at one week of postoperation but returns to the preoperative level after one month. Laser refractive surgery had a short-term modulation of sensory eye dominance.